Determination of the target of monoclonal immunoglobulins: a novel diagnostic tool for individualized MGUS therapy, and prevention and therapy of smoldering and multiple myeloma - Hermouet, Sylvie; Bigot-Corbel, Edith; Harb, Jean (Frontiers in Immunology, 2023)
Subsets of patients diagnosed with a monoclonal gammopathy of undetermined significance (MGUS), smoldering multiple myeloma (SMM) or multiple myeloma (MM), present with a monoclonal immunoglobulin (Ig) specific for an infectious pathogen, including hepatitis C and B viruses (HCV, HBV), Helicobacter pylori and several Herpesviruses. Such cases are likely initiated by infection, since in the context of HCV-or HBV-infected patients, antiviral therapy can lead to the disappearance of antigenic stimulation, control of clonal plasma cells, and reduced or suppressed monoclonal Ig production. Complete remission has been obtained with anti-HCV therapy in refractory MM with a HCV-specific monoclonal Ig, and antiviral treatments significantly improved the probability of survival of MM patients infected with HCV or HBV prior to the diagnosis of MM. Monoclonal Igs may also target glucolipids, particularly glucosylsphingosine (GlcSph), and GlcSph-reducing therapy can lead to complete remission in SMM and MM patients presenting with a GlcSph-specific monoclonal Ig. The present review describes the importance of determining the target of the monoclonal Ig of MGUS, SMM and MM patients, and discusses the efficacy of target-reducing treatments in the management of MGUS, SMM and MM cases who present with a monoclonal Ig reactive against a treatable infectious pathogen or GlcSph.